Catalyst‐Free Dehydrative α‐Alkylation of Ketones with Alcohols: Green and Selective Autocatalyzed Synthesis of Alcohols and Ketones1. (24th November 2013) - Xu, Qing; Chen, Jianhui; Tian, Haiwen; Yuan, Xueqin; Li, Shuangyan; Zhou, Chongkuan; Liu, Jianping
Abstract Direct dehydrative α‐alkylation reactions of ketones with alcohols are now realized under simple, practical, and green conditions without using external catalysts. These catalyst‐free autocatalyzed alkylation methods can efficiently afford useful alkylated ketone or alcohol products in a one‐pot manner and on a large scale by CC bond formation of the in situ generated intermediates with subsequent controllable and selective Meerwein–Pondorf–Verley–Oppenauer‐type redox processes.